Designing Strength Based Work Life Balance Strategies to Enhance Service Quality: A Case Study of S.R. Residence Hotel Phetchabun, Thailand. - Pongpanich, Chinnakrit; Fernando, Maria Socorro (Marrisa) (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Nowadays, every service business must compete with the customer satisfaction for their reputation and success in business. To obtain more competitive advantage and better performance on employees service quality. A company tries to focus on the development of personal work life balance (attitude) and motivation to let employees achieving their task successfully. This research study focuses on employees service quality based on service quality theory. Tangibles – physical facilities, equipment, staff appearance, etc. ,Reliability – ability to perform service dependably and accurately, Responsiveness – willingness to help and respond to customer needs, Assurance – ability of staff to inspire confidence and trust, Empathy – the extent to which caring individualized service is given. The purpose of this study was to examine the impact of work life balance strategies on service quality at the S.R. Residence Hotel, Phetchabun, Thailand. The researcher had conducted mix method research by questionnaires (quantitative) and focus group interviews (qualitative) by using appreciative inquiry (AI) to determined strength-based work life balance on service quality. The questionnaires were distributed to a sample of 60 employees and 40 customers at the S.R. Residence Hotel. The Focus Group interview consisted of 4 group representatives from employees which are Top management, Manager, Low Experience and High Experience employees respectively. The quantitative data was analyzed by using Descriptive mean and standard deviation, Pearson Correlation, Multiple Linear Regression from SPSS to examine and determine the initial impact of work life balance on enhancing service quality at the hotel and qualitative data are using Index of Item Objective Congruence (IOC) with inter coding methods on focus group interview answer to find out the common theme for each questions. The discussion from the research study will develop employee service quality at the S.R. Residence Hotel in the future.